Pola makan dan indikator lemak tubuh pada remaja - Fayasari, Adhila; Julia, Madarina; Huriyati, Emy (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2018)
Background : Previous studies has focused on intakes of individual nutrients and/or foods or food groups to specific effect on health, but there were still not clear about the effect of dieting pattern and food choice to overweight/obesity indicators like BMI-for Age, fat percentage, waist circumference and waist to height ratio and which food group has the most effect to obesity indicators.Objective: This study examined the association of meal pattern to BMI-for Age, fat percentage, waist circumference and waist to height ratio.Methods: This cross sectional study involved 738 individuals aged 15-18 years old adolescents in public school in Kota Yogyakarta. Height and waist circumference were measured by microtoise and metline. Weight and fat percentage were measured by hand-to-foot BIA. BMI-for–age were determined by WHO Antroplus. Dieting pattern was determined by self-reported questionnaire food frequency questionaire which consisted of 91-food item. Data were analyzed by t-test, and linier regression and multiple regression.Results: Overweight and obese were present in 13.41% and 5.43% subjects. In linear regression analysis, legumes, one dish meal, snacks, and sweetened beverages were negatively associated to BMI for age, waist circumference, waist to height ratio and fat pecentage (p<0.05). While in food items analysis, legumes, snacks and sweetened beverages were associated with the increase of waist circumference and fat percentage, while milk and soft drink as protective factor to the increase of fat percentage (-1.70 (-2.40;-1.00); -1.68 (-2.78;-0.58)).Conclusion: In a conclusion, increase in BMI for age and waist circumference are more affected by the intake of high frequency of macronutrients, while increase in fat percentage were associated with sweetened beverages consumption.